Comparison between basal insulin glargine and NPH insulin in patients with diabetes type 1 on conventional intensive insulin therapy - Pešić Milica; Živić Saša; Radenković Saša; Velojić Milena; Dimić Dragan; Antić Slobodan (Vojnosanitetski Pregled)
Background/Aim. Insulin glargine is a long-acting insulin analog that mimics normal basal insulin secretion without pronounced peaks. The aim of this study was to compare insulin glargine with isophane insulin (NPH insulin) for basal insulin supply in patients with type 1 diabetes. Methods. A total of 48 type 1 diabetics on long term conventional intensive insulin therapy (IIT) were randomized to three different regimens of basal insulin substitution: 1. continuation of NPH insulin once daily at bedtime with more intensive selfmonitoring (n = 15); 2. NPH insulin twice daily (n = 15); 3. insulin glargine once daily (n = 18). Meal time insulin aspart was continued in all groups. Results. Fasting blood glucose (FBG) was lower in the glargine group (7.30±0.98 mmol/l) than in the twice daily NPH group (7.47±1.06 mmol/l), but without significant difference. FBG was significantly higher in the once daily NPH group (8.44±0.85 mmol/l; p < 0.05). HbA1c after 3 months did not change in the once daily NPH group, but decreased in the glargine group (from 7.72±0.86% to 6.87±0.50%), as well as in the twice daily NPH group (from 7.80±0.83% to 7.01±0.63%). Total daily insulin doses were similar in all groups but only in the glargine group there was an increase of basal and decrease of meal related insulin doses. The frequency of mild hypoglycemia was significantly lower in the glargine group (6.56±2.09) than in both NPH groups (9.0±1.65 in twice daily NPH group and 8.13±1.30 in other NPH group) (episodes/patients-month, p < 0.05). Conclusion. Basal insulin supplementation in type 1 diabetes mellitus with either twice daily NPH insulin or glargine can result in similar glycemic control when combined with meal time insulin aspart. However, with glargine regimen FBG, HbA1c and frequency of hypoglycemic event are lower. These facts contribute to better patients satisfaction with insulin glargine versus NPH insulin in IIT in type 1 diabetics.